Becoming the other. The role of princes, presbyters and pilgrims in Kyivan Rus′ new Christian identity - Torres Prieto, Susana (Instituto de Estudos Medievais, 2024)
After the late conversion of Kyivan Rus′ in 988, the Orthodox Church became one of the most relevant institutions in the newly Christian polity. From being heathen traders of Scandinavian origin, they eventually became the new Jerusalem, particularly after the Fall of Constantinople. Christianisation was a process that had many political, economic and social ramifications. The present chapter analyses some of the most visible forms of this new Christian identity. On the one hand, the Christian propaganda of the ruling elites, but also the proliferation of religious buildings, which transformed the landscape of Rus′ and, eventually, the growth of local pilgrim’s tales to the Holy Land, whose purpose was to serve as models for others to follow. The appropriation of Byzantine Christian culture and heritage was key in the self-definition of the Rus′ as a Christian people. In this process, Kyivan letters also inherited a Christian geography and cosmogony that were previously unknown to them in their religious dimension and that contributed decisively to situate Kyivan Rus′ within the topography of the Christian oikoumene.
Keywords: Kyivan Rus′; Christianisation; pilgrimages; monastic foundations; Jerusalem; 55 Historia::5504 Historia por épocas::5504.03 Historia medieval; 55 Historia::5506 Historia por especialidades::5506.21 Historia de las religiones; ODS 16 - Paz, justicia e instituciones sólidas